Development of online research tracking system (ProRTS) / Mohammad Hissan Daud - Daud, Mohammad Hissan (2006)
This research project is about developing Online Research Tracking System in FTMSK. The objectives of the research project are to conduct analysis study of research application at FTMSK and process of tracking the progress of a research. The approach used in this development is web development framework application and prototyping modeling. The study investigates about the current system that applied at FTMSK's and the researcher comes out with the requirement for Online Research Tracking System. The researcher developed a prototype to test and verify the requirement gathered. As a result, a prototype of Online Research Tracking System has been developed to enhance the current systems that are still using a manual file system. The proposed system is to make the process easier, efficient and save time by using computerized system. In the end of the research project period, researcher found out that the result is comply with the objective and therefore, all the objective in these research project have been achieved.